2015
DOI: 10.1186/s12944-015-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering efficacy and safety of Ezetimibe combined with rosuvastatin compared with titrating rosuvastatin monotherapy in HIV-positive patients

Abstract: BackgroundHIV-infected patients on antiretroviral therapy frequently develop dyslipidemias and, despite therapy with potent lipid-lowering agents, a high percentage does not achieve guideline recommended lipid targets. In this study, we examined the efficacy of combination treatment with a statin and the cholesterol transport blocker, ezetimibe, vs. monotherapy with a statin in HIV-infected patients not achieving lipid goals.MethodsThis was a 12-week, prospective, randomized, open-label clinical trial. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Atorvastatin and rosuvastatin, the two highest‐intensity statins, have modest interactions with ART and can be safely prescribed for PLHIV with lipid‐lowering effects similar to those for uninfected patients 19 . Addition of ezetimibe to rosuvastatin results in improved lipid indices with no adverse effects compared with dose‐increase of rosuvastatin 20 . A recent study among 7686 HIV/hepatitis C virus‐coinfected and 17 739 HIV ‐monoinfected persons showed that statin initiators had a lower risk of acute liver injury and death within 18 months compared with statin nonusers 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin and rosuvastatin, the two highest‐intensity statins, have modest interactions with ART and can be safely prescribed for PLHIV with lipid‐lowering effects similar to those for uninfected patients 19 . Addition of ezetimibe to rosuvastatin results in improved lipid indices with no adverse effects compared with dose‐increase of rosuvastatin 20 . A recent study among 7686 HIV/hepatitis C virus‐coinfected and 17 739 HIV ‐monoinfected persons showed that statin initiators had a lower risk of acute liver injury and death within 18 months compared with statin nonusers 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Most probably, the anti-HIV-1, EV1, as well as HCV action of ezetimibe is associated with depletion of cholesterol which is required for entry of these viruses into the host cells (Sainz et al, 2012). Importantly, this drug was successfully tested in combination with antiretroviral therapeutics to lower cholesterol levels in serum of HIV-infected patients (Saeedi et al, 2015;Wohl et al, 2008). The question remains whether ezetimibe alone reduces HIV titers in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 11 studies (n = 1926 participants) were eligible for the meta-analysis ( Fig. 1) [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Study Selectionmentioning
confidence: 99%